"Round, red globules floating in a crystalline fluid" – Antoni van Leeuwenhoek's observations of red blood cells and hemocytes. (June 2022) - Davis, Ian M.
Abstract: This article addresses a deficit in the cell biology and hematology literature, specifically regarding Antoni van Leeuwenhoek's central role in observing and describing red blood cells and hemocytes. While the existing literature on the history of hematology usually mentions Antoni van Leeuwenhoek, typically, it is an incomplete summary of his contributions. Leeuwenhoek is cited as one of the three individuals who first saw and described red blood cells through their microscope lenses. Jan Swammerdam and Marcello Malpighi also documented red blood cells in human blood before Leeuwenhoek. The literature fails to mention that Leeuwenhoek commented on red blood "globules, " as well as arthropod hemocytes, at least thirty-five times in thirty-one letters spanning thirty-nine years of correspondence to The Royal Society and others. Some of his descriptive passages were extensive. His observations on blood circulation are a separate set of observations in his letters and are not covered here. Leeuwenhoek viewed various creatures to see if there were characteristics to their blood cells that he could share with the recipients of his letters. He also would view the cells in different chemical and physical environments to understand their properties. Leeuwenhoek's observations of blood corpuscles are discussed in chronological order. Comments included in footnotes by the Committee of Dutch Scientists, who edited the published seventeen volumes of Leeuwenhoek's Alle de Brieven, are also discussed when their comments are relevant.